Horace N. Allen: Missions, Expansionism, Structural Holes, and Social Capital - Kim, Henry (Journal for the sociological integration of religion and society, 2013)
To date, only two scholars (historians) have attempted to research thoroughly the Horace N. Allen Manuscripts (MSS) regarding the first American resident missionary in Korea. This paper makes an important contribution because, to my knowledge, no study has perused the entire Allen MSS and woven a single theme that connects Allen's actions in both Korea and Hawaii. Research on the development of Protestantism in Korea can be generally separated via religious and non-religious factors. In this paper, I emphasize how socio-historic contexts, expansionism, and various missionary activities allowed Allen to fill structural holes and employ social capital for personal and national advancements. I argue that Allen's social connections facilitated America's missionary and expansionistic endeavors in Korea and Hawaii at the turn of the 20th century.